MP46: Clinically significant traumatic intracranial haemorrhage following minor head trauma in older adults: a retrospective cohort study. (May 2020) - Mercier, E.; O'Brien, T.; Mitra, B.; Le Sage, N.; Tardif, P.; Emond, M.; D'Astous, M.
Abstract : Introduction: The primary objective of this study was to determine the incidence of clinically significant traumatic intracranial haemorrhage (T-ICH) following minor head trauma in older adults. Secondary objective was to investigate the impact of anticoagulant and antiplatelet therapies on T-ICH incidence. Methods: This retrospective cohort study extracted data from electronic patient records. The cohort consisted of patients presenting after a fall and/or head injury and presented to one of five ED between 1st March 2010 and 31st July 2017. Inclusion criteria were age ≥ 65 years old and a minor head trauma defined as an impact to the head without fulfilling criteria for traumatic brain injury. Results: From the 1, 000 electronic medical records evaluated, 311 cases were included. The mean age was 80.1 (SD 7.9) years. One hundred and eighty-nine (189) patients (60.8%) were on an anticoagulant (n = 69), antiplatelet (n = 130) or both (n = 16). Twenty patients (6.4%) developed a clinically significant T-ICH. Anticoagulation and/or antiplatelets therapies were not associated with an increased risk of clinically significant T-ICH in this cohort (Odds ratio (OR) 2.7, 95% CI 0.9-8.3). Conclusion: In this cohort of older adults presenting to the ED following minor head trauma, the incidence of clinically significant T-ICH was 6.4%.